2014
DOI: 10.1115/1.4028510
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Predictive Modeling and Compensation of Geometric Deviations of Three-Dimensional Printed Products

Abstract: Geometric fidelity of 3D printed products is critical for additive manufacturing (AM) to be a direct manufacturing technology. Shape deviations of AM built products can be attributed to multiple variation sources such as substrate geometry defect, disturbance in process variables, and material phase change. Three strategies have been reported to improve geometric quality in AM: (1) control process variables x based on the observed disturbance of process variables Ax, (2) control process variables x based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(41 citation statements)
references
References 16 publications
0
39
0
1
Order By: Relevance
“…In contrast, Huang, Zhang, Sabbaghi, and Dasgupta [12] conceived of a distinct functional modeling framework that effectively accounts for the correlation in deviation between different directions, and decouples geometric shape complexity from deviation modeling and compensation. Further advances and experiments under their framework include in-plane deviation modeling for polygons and free-form shapes [11,16,25], interference modeling for discretized compensation plans [24], and out-of-plane deviation modeling for 3D shapes [14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Huang, Zhang, Sabbaghi, and Dasgupta [12] conceived of a distinct functional modeling framework that effectively accounts for the correlation in deviation between different directions, and decouples geometric shape complexity from deviation modeling and compensation. Further advances and experiments under their framework include in-plane deviation modeling for polygons and free-form shapes [11,16,25], interference modeling for discretized compensation plans [24], and out-of-plane deviation modeling for 3D shapes [14].…”
Section: Introductionmentioning
confidence: 99%
“…[20] studied the impact of different process parameters on part shrinkage during SLS process, and used Taguchi method to develop scaling models along x, y and z directions to compensate for the shrinkage. Huang et al [21,22] investigated the offline shape-shrinkage compensation for the individual layer contours using a statistical approach. Wang et al [23] reported a Neural Network based approach for establishing the relation between AM process parameters and shrinkage ratio for parts fabricated using SLS.…”
Section: Previous Thermal Compensation Approaches For Am Processesmentioning
confidence: 99%
“…Zha and Anand [24] presented a geometric approach to improve errors of part by modifying input stereolithography (STL) models in AM processes. Huang et al [25][26][27] conducted research using statistical approaches to model and predict in-plane shrinkage and out-of-plane deformation of different parts, and derive compensation to improve accuracy of built part in the MIP-SL process. All these research have effects on improving errors of built parts in AM processes.…”
Section: Introductionmentioning
confidence: 99%